PERAN INTERNATIONAL PRIVATE INVESTIGATOR DALAM MEMPERKUAT SISTEM PERADILAN PIDANA INTERNASIONAL: PENDEKATAN HISTORIS - Deiny Setiyawan (Faculty of Law Universitas Sebelas Maret, 2023)
This article discusses the role of Private International Criminal Investigators in international justice practices during the ICTY to ICC periods. This article uses the method of writing international law with statutory approach, case approach, and historical approach. The legal material used in writing this law is in the form of primary legal material originating from laws and regulations, and secondary law originating from library research by examining theories, dogmas, findings, and previous documentation in related fields. The results of this study indicate that the role of private investigators in international crime investigations varies depending on the existing international judicial institutions. In various ICTY performances, private investigators are used to assist with special reporting procedures by voluntarily and actively involving independent organizations such as OSCE, ECMM, and Human Rights Watch. In the performance of ICTR, private investigators consisting of third organizations, individual researchers from educational institutions, to advocates and NGO institutions, are involved in reports handled by the Special Committee to be able to prove indications of international crimes in Rwanda. Meanwhile, in the performance of the ICC, the involvement of private investigators has increased, for example in the Lubanga and Katanga cases, where information findings and field evidence collected by third parties were actively used in a series of trials indicating international crimes